Multicenter Study of 6-Month Clinical Outcomes After Descemet Membrane Endothelial Keratoplasty. Issue 12 (December 2017) - Oellerich, Silke; Baydoun, Lamis; Peraza-Nieves, Jorge; Ilyas, Abbas; Frank, Laurence; Binder, Perry S.; Melles, Gerrit R. J.
Abstract : Purpose: To report the 6-month clinical outcomes of a large cohort of Descemet membrane endothelial keratoplasty (DMEK) eyes operated by 55 starting or experienced surgeons. Methods: This is a retrospective, multicenter, interventional, cohort study with a total of 2485 eyes. Best-corrected visual acuity (BCVA), endothelial cell density (ECD) decrease, and intra- and post-operative complications were evaluated. Three groups based on case order were compared: group I (cases 1–24), group II (cases 25–99), and group III (cases ≥100). Forty-nine percent of the surgeons were in their learning curve (<25 cases), representing 10.4% of the surgeries. Results: Six months after DMEK, BCVA improved in 90.5% of eyes, remained unchanged in 4.6%, and deteriorated in 4.9% (n = 1936); 75.4% of eyes reached a BCVA of ≥20/40 (≥0.5), 45.4% ≥20/25 (≥0.8), and 25.8% ≥20/20 (≥1.0) (n = 1959) and ECD decreased by 40% (±19) (n = 1272, P < 0.05). BCVA and ECD outcomes did not differ between groups I and III ( P > 0.05). Intraoperative complications were reported for 9.4% of eyes, whereas graft detachment was the main postoperative complication (27.4%), with lower intra- and post-operative complication rates in group III than group I ( P < 0.05). Rebubbling was performed in 20.1% of eyes; 13.8% required secondary keratoplasty within 6 months. Conclusions: DMEK is applicable for surgeons in various settings with good clinical outcomes. After an arbitrary learning curve (<25 cases), virtually all transplant-related complications declined with experience. Notably, surgeons with a higher annual caseload may pass faster through their learning curve than surgeons performing their first surgeries over an extended period. Abstract : Supplemental Digital Content is Available in the Text.